2015
DOI: 10.1002/acn3.276
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mechanism of recurrent mutations of SCN8A in epileptic encephalopathy

Abstract: ObjectiveThe early infantile epileptic encephalopathy type 13 (EIEE13, OMIM #614558) results from de novo missense mutations of SCN8A encoding the voltage‐gated sodium channel Nav1.6. More than 20% of patients have recurrent mutations in residues Arg1617 or Arg1872. Our goal was to determine the functional effects of these mutations on channel properties.MethodsClinical exome sequencing was carried out on patients with early‐onset seizures, developmental delay, and cognitive impairment. Two mutations identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 41 publications
4
92
0
Order By: Relevance
“…These pathogenic mutations arise de novo in affected individuals and generate gain-of-function missense mutations that increase the activity of sodium channel Na v 1.6 (Wagnon et al, 2016). Two commonly observed changes in Na v 1.6 are impaired channel inactivation, and a hyperpolarizing shift in voltage dependence of activation that results in premature channel opening (Barker et al, 2016; Blanchard et al, 2015; Estacion et al, 2014; Veeramah et al, 2012; Wagnon et al, 2016). SCN8A encephalopathy is characterized by seizure onset within the first 18 months of life, typically by 4 months of age (Larsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These pathogenic mutations arise de novo in affected individuals and generate gain-of-function missense mutations that increase the activity of sodium channel Na v 1.6 (Wagnon et al, 2016). Two commonly observed changes in Na v 1.6 are impaired channel inactivation, and a hyperpolarizing shift in voltage dependence of activation that results in premature channel opening (Barker et al, 2016; Blanchard et al, 2015; Estacion et al, 2014; Veeramah et al, 2012; Wagnon et al, 2016). SCN8A encephalopathy is characterized by seizure onset within the first 18 months of life, typically by 4 months of age (Larsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SCN1A encoding Nav1.1 has been shown to be the most frequent target of mutations and is responsible to a variety of epilepsy syndromes8. Recently, much attention has been paid to SCN8A encoding Nav1.6 involved in the pathogenesis of epilepsy910111213141516.…”
mentioning
confidence: 99%
“…Nav1.6 contributes to the production of tetrodotoxin-sensitive (TTX-S) transient current, persistent current, and resurgent current19. Several mutations of SCN8A have been recently identified and have been found to be functionally associated with epilepsy syndrome910111620. It has been found that Nav1.6 plays a role in facilitating the hyperexcitability of medial entorhinal cortex layer II neurons at 7 days after electrical induction of status epilepticus12.…”
mentioning
confidence: 99%
“…Interestingly, mutation of the corresponding leucine residue in SCN1A resulted in impaired channel inactivation (Kahlig et al 2008), a common feature of SCN8A mutations in epileptic encephalopathy (Wagnon et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Ten patient mutations of SCN8A have been evaluated with functional tests in transfected cells (Veeramah et al 2012; de Kovel et al 2014; Estacion et al 2014; Blanchard et al 2015; Wagnon et al 2016). In eight of the 10 cases, gain-of-function effects were observed.…”
Section: Introductionmentioning
confidence: 99%